Surface engineering of titanium alloys for the motorsports industry - Dong,H.; Bell, T.; Mynot, A. (Sports Engineering, 1999)
The present paper demonstrates, by way of example, a number of major steps towards titanium designer surfaces. The motorsports industry has recognised the potential of surface engineered titanium components and it is envisaged that the new Millennium will see wide applications of titanium in the motorsports industry.